2022
DOI: 10.1149/1945-7111/ac67f8
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Core-Shell and Agglomerate Particle Design for All-Solid-State Batteries

Abstract: All-solid state lithium polymer batteries are promising next-generation batteries with high safety and energy density. Their success depends on an improved design with a tailored cathode manufacturing process. To facilitate a knowledge-driven optimal design of the cathode, a model-based analysis on the impact of the cathode particle structure on the electrochemical cell performance wais conducted. During production of solid-state cathodes, small active material particles such as lithium-iron phosphate tend to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…So far, few studies have been conducted on the microstructure modelling of ASSB with physics-based modelling. Cistjakov et al 16 modelled the influence of cathode particle structures on discharge behaviour in a polymer-based battery with agglomerate and core-shell particles. He demonstrated that cells with homogeneous agglomerate particles have the highest capacity at low C-rates.…”
mentioning
confidence: 99%
“…So far, few studies have been conducted on the microstructure modelling of ASSB with physics-based modelling. Cistjakov et al 16 modelled the influence of cathode particle structures on discharge behaviour in a polymer-based battery with agglomerate and core-shell particles. He demonstrated that cells with homogeneous agglomerate particles have the highest capacity at low C-rates.…”
mentioning
confidence: 99%